The Infection of Masticator Space Caused by Pericoronitis of Lower Third Molar - Hiranrus, Anong (Journal of Health Science of Thailand, 1994)
The treatment of infection of the masticator spaces was reported and discussed with severe swelling and trismus. Pericoronitis of the gingival flap of partially erupted lower third mom: is usually found as the cause of masticator spaces infection. The treatment consisted of hydration, high dosed antibiotics and surgical decompression.